Analysis of the distributional effects of COVID19 and state-led remedial measures in South Africa - Helen Barnes; Gabriel Espi-Sanchis; Murray V. Leibbrandt; David McLennan; Michael Noble; Jukka Pirttilä; Wynnona Steyn; Brenton van Vrede; Gemma Clare Wright (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper explores the impact of the first wave of the COVID-19 pandemic in South Africa on income poverty and inequality in South Africa. Using a static tax-benefit microsimulation model with input datasets that were adjusted to reflect people's earned incomes just before the pandemic (March 2020) and during the first national lockdown (April 2020), we investigate how well the social protection system in South Africa was able to mitigate the economic losses to the public. We take into account both the existing benefit system that was in place before the crisis and the role of the new policy measures that were introduced in April, May, and June 2020.
Keywords: C63; C81; H24; D31; 330; social policy; tax-benefit microsimulation; income distribution; South Africa; COVID-19 pandemic